Studies of Degradation Kinetics of a 5-HT3 Antagonist, Ramosetron Hydrochloride: Effects of Temperature - Hossain, Md Mokaram; Jalil, Reza ul; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Ramosetron hydrochloride is the hydrochloride salt of ramosetron, a selective serotonin (5-HT3) receptor antagonist with potential antiemetic activity. Upon administration, ramosetron selectively binds to and blocks the activity of 5-HT subtype 3 (5-HT3) receptors located in the vagus nerve terminal and the vomiting center of central nervous system (CNS), suppressing chemotherapy-induced nausea and vomiting. Degradation of Ramosetron HCl was conducted with 0.1N NaOH at 60°C, 70°C and 80°C to study the reaction kinetics. The reaction rate constants (k) for degradation at 60°C, 70°C and 80°C were -2.2680 molL-1s-1 , -3.3714 molL-1s-1 and -5.3686 molL-1s-1 for zero order and -1.05 x 10-2s-1, -1.60 x 10-2s-1 and -2.70 x 10-2s-1 for first order kinetics, respectively. The activation energy of Ramosetron HCl was found as 10.05 kcalmol-1 by using Arrhenius equation. Dhaka Univ. J. Pharm. Sci. 17(2): 167-173, 2018 (December)